Heat transfer from pulsating flow in a channel filled with porous media - Kim, S.Y.; Kang, B.H.; Hyun, J.M. (1994)
A numerical study is made of heat transfer characteristics from forced pulsating flow in a channel filled with fluid-saturated porous media. The channel walls are assumed to be at uniform temperature. The Brinkman-Forchheimer-extended Darcy model is employed. The time-dependent, two-dimensional governing equations are solved by using finite-volume techniques. Numerical solutions are obtained for quasi-steady periodic states. Flow and temperature fields are examined over ranges of the principal parameters, i.e. the amplitude of flow pulsation A, the pulsation frequency parameter M [≡H( ω 2ν)1 2], the Darcy number Da (≡ K H2), the thermal conductivity ratio Rκ (≡ κeff κ), and the heat capacity ratio Rc {≡ (ρvariantCp)eff [ε(ρvariantCp)]}. The impact of pulsation is discernible in the cycle-averaged temperature distribution. In comparison with the case of non-pulsating flow, the presence of flow pulsation brings forth a reduction in heat transfer in the entrance region and an enhancement of heat transfer at moderate downstream regions. Farther downstream, the influence of pulsation is meager. The magnitudes of changes in heat transfer depend upon A, M, Da, Rκ, and Rc. The effect of pulsation on heat transfer between the channel wall and the fluid is more pronounced for small M and large A. Explicit influences of Da, Rκ, and Rc on the flow and heat transport characteristics are also scrutinized. ？ 1994.
Keywords: Heat Transfer; Porous Media-Flow Through; Pulsating Flow; Channel flow; Finite element method; Mathematical models; Porous materials; Pulsatile flow; Specific heat; Temperature distribution; Thermal conductivity; Wall flow; Brinkman-Forchheimer extended Darcy model; Darcy number; Finite volume method; Forced pulsating flow; Pulsation amplitude; Pulsation frequency; Heat transfer